Analisis Daya Gabung dan Korelasi Karakter Jumlah Buah Kakao pada Persilangan Setengah Dialel - Nur Kholilatul Izzah; Ilham Nur Ardhi Wicaksono; Cici Tresniawati; Edi Wardiana (Jurnal Tanaman Industri dan Penyegar, 2019)
Analysis of combining ability and correlation between characters in cacao plays an important role and benefits in an effort to obtain superior high-yield genetic material. This analysis makes it easy to find out the best combination of parents in producing superior progeny. The study aimed to analyze the combining ability and correlation of cacao pod numbers in F1 population generated from half-diallel crossing. The study was conducted at Pakuwon Experimental Station, Sukabumi, West Java, at an altitude of 450 m above sea level with Latosol soil type and B climate type (Schmidt and Fergusson), from 2014 until 2018. The experiment was arranged using a randomized block design (RBD) with 10 combinations of half-diallel crossing method that were repeated three times. The parental genotypes used were ICCRI 03, TSH 858, DR 1, ICS 13, and SCA 6. The variables observed were the number of healthy pods, number of rotten pods, number of cherelle wilts, and total pod numbers. The combining ability was analyzed using the Griffing 4 method, while correlation analysis was carried out phenotypically and genotypically.The results showed the action of non-additive genes in the F1 generation and three combinations of crosses, namely ICCRI 03 x TSH 858, TSH 858 x DR 1, and ICS 13 x SCA 6 had the opportunity to be developed into superior hybrids. In addition, it is known that there were phenotypic and genotypic positive correlations between the observed pod component characters.